CHEMOKINES: A POTENTIAL THERAPEUTIC TARGET FOR THE STABILISATION OF VULNERABLE PLAQUE - Bradley Tucker; Sanjay Patel (European Medical Journal Cardiology, 2019)
The introduction of lipid lowering medications was initially thought to provide a solution to the growing burden of coronary heart disease. However, 30 years later, the rates of acute coronary syndrome remain unacceptably high. This realisation forced cardiovascular scientists to look beyond lipids and led to the now widely accepted understanding of atherosclerosis pathobiology: immune-facilitated lipid retention with focal and generalised chronic inflammation. A fundamental component of this inflammatory process is chemokines: a class of cytokines characterised by their ability to facilitate cell recruitment, although it is now known that their function extends beyond chemotaxis. Mounting evidence suggests that chemokines are essential for the destabilisation and subsequent rupture of atherosclerotic plaque. Therefore, chemokine pathways provide a novel therapeutic target for plaque stabilisation. This review addresses the role of chemokines in regulating plaque vulnerability and discusses therapeutic approaches targeted at manipulating chemokine pathways.